A estrat??gia de replica????o aplicada ??s t??cnicas de gerenciamento de projetos de TI. - Duarte, C??ssio Chagas Montenegro (2012)
This study evaluates how to establish a theoretical model of project management that is applicable to the area of IT, from the knowledge of strategic replication techniques applied to traditional project management. It was used the theoretical literature associated with both focused on the replication strategy as well as the literature focused on the traditional project management, focusing on its application in business of Information Technology. From the literature developed in the first part of the work, it was prepared twenty-three propositions of study that formed the basis for the development of field research in four major companies that develop projects of Information Technology. The methodology of the study predicted the development of the method of multiple case study, whereby the information obtained in the companies were analyzed together, and so cross, allowing the identification of more robust theoretical model design pattern to be replicated. Empirical evidence suggests that there is a model project adheres to the research problem. It was evident that it is possible to building the model for IT projects in order to replicate it in future derivative projects. Even though this model to meet the challenge of replicating the nontrivial non-routine activities, unique, peculiar and inherent to the life cycle of projects. It was evident that the maturation of this type of project requires a long period of time, until it reaches the final level of standard, since it requires a considerable effort, which depends on the learning acquired at the end of an extensive and continuous process, consisting of many interactions, refinements and sponsorship of high intensive management, which ultimately results in its incorporation into the company culture.